School Enrichment Activities as a Strategy to Contribute to the School Inclusion of Students With High Ability/Giftedness - Soraia Napoleão Freitas; Andréia Jaqueline Devalle Rech (Arizona State University, 2015)
This article aims to discuss the school inclusion of students with high ability/giftedness (AH/SD), given that educational inclusion is present in most Brazilian schools. However, this still seeks to be an effective school inclusion that goes beyond ensuring enrollment of students with special educational needs (NEEs) in regular school. Thus, it is intended that public policy efforts to move that student to remain in school due to the quality of teaching and learning which this one is entitled. To collaborate with this discussion will be presented the investigation of educational inclusion of a student with indicators AH/SD, registered in the early grades of a public school in the city of Santa Maria, Rio Grande do Sul. The research set is qualitative, descriptive, and of case study type. Data were collected from the observation of everyday classroom in which the student was enrolled, also featured school enrichment activities, and interviews with the teacher and the parents of the student. Subsequently the interview was transcribed and the data were analyzed descriptively relating them to the participants that the researchers conducted observations in the school environment. At the end of the research it was found that the pedagogical strategies that the teacher used did not contribute to the school inclusion of student with indicators of AH/SD. Unfortunately, these data reveal that the inclusion of these school students still have a long way to go, considering that many teachers still do not recognize that students with AH/SD present NEEs, so many of these students are still invisible in classrooms.